2019
DOI: 10.3117/rootres.28.59
|View full text |Cite
|
Sign up to set email alerts
|

Title

Abstract: We analyzed the effects of plowing on root systems and root lodging of maize (Zea mays L.) in comparison with rotary tilling in upland fields converted from paddy fields in Gleysol. The percentage of soil water potential more than-3.1 kPa before the 6th leaf stage tended to be smaller following plowing than rotary tilling; and drainage was improved with plowing. Soil temperature at depths of 5 and 10 cm during the growing season was similar between the tillage treatments. Dry weight and leaf area index did not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…Previous reports (Shinoto et al, 2019a(Shinoto et al, , 2018a indicate that the root system is shallower in PT than in RT under fertilized conditions. Furthermore, soil hardness at soil depths of 5-20 cm is higher in PT than in RT, and a higher proportion of fertilizer is distributed in the surface layer in PT than in RT (Shinoto et al, 2018b).…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Previous reports (Shinoto et al, 2019a(Shinoto et al, , 2018a indicate that the root system is shallower in PT than in RT under fertilized conditions. Furthermore, soil hardness at soil depths of 5-20 cm is higher in PT than in RT, and a higher proportion of fertilizer is distributed in the surface layer in PT than in RT (Shinoto et al, 2018b).…”
Section: Discussionmentioning
confidence: 87%
“…In upland fields converted from paddy fields, growth, grain yield, and nitrogen absorption of maize are not significantly different between rotary tilling and plowing tillage; however, the root system of maize does differ between plowing tillage and rotary tilling (Shinoto et al, 2018a(Shinoto et al, , 2017(Shinoto et al, , 2018b). The root system at maturity or at the milk stage tends to be shallower with plowing tillage than with rotary tilling (Shinoto et al, 2019a(Shinoto et al, , 2018a. Others have also reported that the root system of maize becomes shallower in untilled or shallowly cultivated soils because the root length in the surface layers is longer (Ball-Coelho et al, 1998;Barber, 1971;Bauder et al, 1985).…”
Section: Introductionmentioning
confidence: 98%